A kind of weather-resistant industrial coating and preparation method thereof
By combining hexenyl ultraviolet absorber, modified epoxy resin and modified glass flakes with self-healing and curing agent, weather-resistant industrial coatings are prepared, which solves the problem of poor weather resistance of traditional coatings and achieves good anti-aging and flame retardant and self-healing performance, extending service life.
Patent Information
- Application Number
- CN202411433061.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-10-15
AI Technical Summary
Traditional industrial coatings are prone to fading, pulverizing, cracking and peeling under long-term ultraviolet light, resulting in poor weather resistance and affecting their aesthetic performance and protective effect.
Using a combination of hexenyl ultraviolet absorber, modified epoxy resin emulsion, modified glass flakes and self-healing curing agent, the modified epoxy resin and modified glass flakes are prepared through reaction, and combined with self-healing curing agent to form a weather-resistant industry Paints improve anti-aging, flame retardant and corrosion resistance.
It significantly improves the anti-aging performance, flame retardant performance and self-repair performance of the paint, extends its service life, and enhances its resistance to ultraviolet light and corrosion.
Smart Images

Figure FDA0005142916750000021
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, in particular to a weather-resistant industrial coating and a preparation method thereof. Background Art
[0002] Industrial coatings are an important pillar of the coatings industry, accounting for a large proportion of the total output of coatings. It refers to the general term for coating materials that are applied to the surface of objects and have protective, decorative or special properties (such as insulation, anti-corrosion, marking, etc.). The application fields of industrial coatings are very wide, including but not limited to automobiles, aircraft, ships, buildings, wooden furniture, highways and other fields. In these fields, industrial coatings can provide multiple functions such as anti-corrosion, anti-rust, decoration, conductivity, flame retardancy, etc., protect the surface of products, prevent products from being eroded by the external environment and substances, and extend their service life. Traditional industrial coatings are mostly composed of resins, pigments, additives and solvents, and have poor weather resistance. Especially for industrial coatings used outdoors, aging phenomena such as fading, powdering, cracking, peeling and even whole-layer shedding will occur under long-term ultraviolet light, which seriously damages the aesthetic properties and protective effects of industrial coatings. Therefore, it is necessary to develop a weather-resistant industrial coating to enhance the anti-aging ability of industrial coatings, expand the scope of use of industrial coatings, and extend the service life of industrial coatings, which has important practical significance and broad market prospects. Summary of the invention
[0003] The object of the present invention is to provide a weather-resistant industrial coating and a preparation method thereof, so as to solve the problems existing in the prior art.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0005] A weather-resistant industrial coating, wherein the weather-resistant industrial coating is prepared by reacting a hexene-based ultraviolet absorber, methacrylic acid and bisphenol A epoxy resin E51 to obtain a modified epoxy resin emulsion; polymerizing and growing 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide and methylphenylsilanediol on pre-modified glass flakes to obtain modified glass flakes; and uniformly mixing the modified epoxy resin emulsion, the modified glass flakes, a self-repairing curing agent and a defoaming agent to obtain the coating;
[0006] The self-repairing curing agent is prepared by reacting 2-furanmethylamine and N-(2-aminopropyl)maleimide;
[0007] The hexenyl ultraviolet absorber is prepared by reacting 6-chloro-1-hexene and 2,3-bis(2,4,5-trimethyl-3-thienyl)maleimide;
[0008] The pre-modified glass flakes are prepared by reacting 3-chloropropyltriethoxysilane and glass flakes.
[0009] A method for preparing a weather-resistant industrial coating, the method comprising the following preparation steps:
[0010] (1) Mix hexyl ultraviolet absorber, methacrylic acid, benzoyl peroxide and n-butanol in a mass ratio of 1:(1-2):(0.03-0.05):(6-8) to obtain a mixed monomer reaction solution; mix bisphenol A epoxy resin E51, ethylene glycol monobutyl ether and n-butanol in a mass ratio of 1:(1-2):(2-3) to obtain a mixed monomer reaction solution, and stir at 100-110°C and 300-500 r / min for 10-20 min. Add a mixed monomer reaction liquid of 1 to 1.2 times the mass of bisphenol A epoxy resin E51 dropwise at a uniform speed within 30 minutes, raise the temperature to 120 to 122°C, continue stirring and reacting for 2 to 3 hours, cool to 80 to 85°C, add a salt-forming agent of 0.1 to 0.2 times the mass of bisphenol A epoxy resin E51 and deionized water of 2 to 3 times the mass of bisphenol A epoxy resin E51, stir at 600 to 700 r / min for 1 to 2 hours to obtain a modified epoxy resin emulsion;
[0011] (2) Pre-modified glass flakes, 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide and acetonitrile are mixed uniformly in a mass ratio of 1:(2-3):(26-30), stirred at 80-85°C and 300-500 r / min for 10-15 min, and in a nitrogen atmosphere, 0.7-0.8 times the molar amount of 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide of methylphenylsilanediol is added dropwise over 10 min, and the reaction is continued by stirring for 10-12 h, filtered, washed with acetonitrile 3-5 times, and dried at 50-60°C under vacuum conditions for 8-10 h to obtain modified glass flakes;
[0012] (3) Weigh 95-105 parts of modified epoxy resin emulsion, 3-5 parts of modified glass flakes, 18-20 parts of self-healing curing agent, and 0.5-0.7 parts of defoaming agent by mass, mix them evenly, stir at 300-500 r / min for 5-10 min, adjust the viscosity to 60-80 KU with deionized water, and prepare a weather-resistant industrial coating.
[0013] As an optimization, the preparation method of the hexenyl ultraviolet absorber in step (1) is as follows: 6-chloro-1-hexene and 2,3-bis(2,4,5-trimethyl-3-thienyl)maleimide are added in a molar ratio of 1:1 to toluene with a mass of 8 to 10 times that of 6-chloro-1-hexene, and triethylamine with a mass of 0.03 to 0.05 times that of 6-chloro-1-hexene is added, and the mixture is stirred at 50 to 60°C and 300 to 500 r / min for 3 to 4 hours, and dried at 50 to 60°C under vacuum conditions for 8 to 10 hours to obtain the hexenyl ultraviolet absorber.
[0014] As an optimization, the salt-forming agent in step (1) is N,N-dimethylaminoethanol.
[0015] As an optimization, the preparation method of the pre-modified glass flakes in step (2) is: mix the glass flakes and anhydrous ethanol in a mass ratio of 1:(20~30), add silane hydrolyzate in an amount of 8~10 times the mass of the glass flakes, stir and react at 50~60°C and 300~500r / min for 2~3h, filter, wash with anhydrous ethanol 3~5 times, and dry at 70~80°C under vacuum conditions for 8~10h to obtain pre-modified glass flakes.
[0016] As an optimization, the preparation method of the silane hydrolyzate is: 3-chloropropyltriethoxysilane and anhydrous ethanol are mixed evenly in a mass ratio of 1:(40~50), the pH is adjusted to 4~6 with a 1 mol / L oxalic acid aqueous solution, and the mixture is stirred at 10~30°C and 300~500r / min for 50~60min to prepare a silane hydrolyzate.
[0017] As an optimization, the thickness of the glass flakes is 2~3μm and the diameter of the flakes is 10~20μm.
[0018] As an optimization, the preparation method of the self-healing curing agent in step (3) is: add 2-furanmethylamine and N-(2-aminopropyl)maleimide in a molar ratio of 1:1 to N,N-dimethylformamide which is 8 to 10 times the mass of 2-furanmethylamine; under nitrogen protection, stir and react at 60 to 70°C and 300 to 500 r / min for 2 to 3 hours; and dry at 50 to 60°C for 8 to 10 hours under vacuum conditions to obtain a self-healing curing agent.
[0019] As an optimization, the model of the defoaming agent in step (3) is THIX-318.
[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0021] When preparing the weather-resistant industrial coating, the present invention comprises the following steps: 6-chloro-1-hexene and 2,3-bis(2,4,5-trimethyl-3-thienyl)maleimide are reacted to obtain a hexenyl ultraviolet absorber; the hexenyl ultraviolet absorber, methacrylic acid and bisphenol A epoxy resin E51 are reacted to obtain a modified epoxy resin emulsion; 3-chloropropyltriethoxysilane and glass flakes are reacted to obtain pre-modified glass flakes; 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide and methylphenylsilanediol are polymerized and grown on the pre-modified glass flakes to obtain the modified glass flakes; 2-furanmethylamine and N-(2-aminopropyl)maleimide are reacted to obtain a self-repairing curing agent; the modified epoxy resin emulsion, the modified glass flakes, the self-repairing curing agent and the defoaming agent are uniformly mixed to obtain the weather-resistant industrial coating.
[0022] Firstly, 6-chloro-1-hexene and 2,3-bis(2,4,5-trimethyl-3-thienyl)maleimide are reacted to obtain a hexenyl ultraviolet absorber, and a carbon-carbon double bond is introduced into the hexenyl ultraviolet absorber; the hexenyl ultraviolet absorber contains a heterocyclic group-substituted diarylethene structure, and the heterocyclic group-substituted diarylethene has a conjugated six-electron hexatriene mother structure, and under the excitation of ultraviolet light, it undergoes a cis-rotational ring closure to generate a closed ring body, and under the irradiation of visible light, it can undergo the opposite change to generate an open ring body, thereby dissipating the ultraviolet light energy and giving the weather-resistant industrial coating excellent anti-aging performance; the hexenyl ultraviolet absorber and methacrylic acid are grafted onto bisphenol A epoxy resin E51 through a free radical reaction, and a hydrophilic group carboxyl group is introduced, and the carboxyl group reacts with a salt-forming agent to generate a carboxylate, so that the bisphenol A epoxy resin E51 has amphiphilicity, and a modified epoxy resin emulsion is obtained.
[0023] Secondly, 3-chloropropyltriethoxysilane and glass flakes are reacted to obtain pre-modified glass flakes, chlorine atoms are introduced into the pre-modified glass flakes, and 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide and methylphenylsilanediol are dehydrochlorinated and polymerized on the pre-modified glass flakes to obtain modified glass flakes; phosphorus elements and Si-O bonds are introduced into the modified glass flakes, which decompose to produce polyphosphate and silicon dioxide during combustion, which can promote the formation of a honeycomb-like tight carbon layer structure during combustion, reduce the generation of combustible gas, synergistically flame retardant, and give the weather-resistant industrial coating excellent flame retardant properties; glass flakes can extend or hinder the diffusion and penetration path of corrosive media, thereby improving the corrosion resistance of weather-resistant industrial coatings, and the glass flakes are modified to increase the compatibility of the glass flakes with the matrix resin, so that the glass flakes are evenly dispersed in the coating, and the barrier effect of the glass flakes is fully exerted.
[0024] Finally, 2-furanmethylamine and N-(2-aminopropyl)maleimide are reacted to obtain a self-healing curing agent. The furan group on 2-furanmethylamine and the maleimide group on N-(2-aminopropyl)maleimide undergo a Diels-Alder addition reaction to form a thermally reversible structure, which gives the weather-resistant industrial coating self-healing properties. At the same time, two amino groups are introduced into the self-healing curing agent. The amino groups introduced into the self-healing curing agent can react with the phosphorus-chlorine bonds on the modified glass flakes and the epoxy groups on the bisphenol A epoxy resin E51 to form a coating. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0026] Embodiment 1: A method for preparing a weather-resistant industrial coating, the method for preparing the weather-resistant industrial coating comprising the following preparation steps:
[0027] (1) 6-chloro-1-hexene and 2,3-bis(2,4,5-trimethyl-3-thienyl)maleimide were added in a molar ratio of 1:1 to toluene (8 times the mass of 6-chloro-1-hexene), and triethylamine (0.03 times the mass of 6-chloro-1-hexene) was added, and the mixture was stirred at 50°C and 300 r / min for 4 hours, and dried at 50°C for 10 hours under vacuum conditions to obtain a hexenyl ultraviolet absorber; the hexenyl ultraviolet absorber, methacrylic acid, benzoyl peroxide, and n-butanol were mixed uniformly in a mass ratio of 1:1:0.03:6 to obtain a mixed monomer reaction solution; Bisphenol A epoxy resin E51, ethylene glycol monobutyl ether and n-butanol were mixed uniformly in a mass ratio of 1:1:2, stirred at 100°C and 300 r / min for 20 min, and a mixed monomer reaction liquid of 1 times the mass of bisphenol A epoxy resin E51 was uniformly added dropwise within 30 min, the temperature was raised to 120°C, and the stirring reaction was continued for 3 h, the temperature was lowered to 80°C, and N,N-dimethylaminoethanol of 0.1 times the mass of bisphenol A epoxy resin E51 and deionized water of 2 times the mass of bisphenol A epoxy resin E51 were added, and the mixture was stirred at 600 r / min for 2 h to obtain a modified epoxy resin emulsion;
[0028] (2) 3-Chloropropyltriethoxysilane and anhydrous ethanol were mixed at a mass ratio of 1:40, the pH was adjusted to 4 with a 1 mol / L oxalic acid aqueous solution, and the mixture was stirred at 10°C and 300 r / min for 60 min to prepare a silane hydrolyzate; glass flakes and anhydrous ethanol were mixed at a mass ratio of 1:20, 8 times the mass of the glass flakes was added with the silane hydrolyzate, and the mixture was stirred at 50°C and 300 r / min for 3 h, filtered, washed with anhydrous ethanol for 3 times, and dried at 70°C under vacuum for 10 h to prepare a pre-modified glass flake; the pre-modified glass flakes and 3,9-dichloro-2, 4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide and acetonitrile were mixed uniformly in a mass ratio of 1:2:26, stirred at 80°C and 300 r / min for 15 min, and in a nitrogen atmosphere, 0.7 times the molar amount of 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide methylphenylsilanediol was uniformly added dropwise within 10 min, and the reaction was continued with stirring for 12 h, filtered, washed with acetonitrile 3 times, and dried at 50°C for 10 h under vacuum conditions to obtain modified glass flakes;
[0029] (3) Add 2-furanmethylamine and N-(2-aminopropyl)maleimide in a molar ratio of 1:1 to N,N-dimethylformamide (8 times the mass of 2-furanmethylamine), stir and react at 60°C and 300 r / min for 3 h under nitrogen protection, and dry at 50°C for 10 h under vacuum conditions to obtain a self-healing curing agent; weigh 95 parts of modified epoxy resin emulsion, 3 parts of modified glass flakes, 18 parts of self-healing curing agent, and 0.5 parts of defoaming agent, and mix them evenly. Stir at 300 r / min for 10 min, adjust the viscosity to 60 KU with deionized water to obtain a weather-resistant industrial coating.
[0030] Embodiment 2: A method for preparing a weather-resistant industrial coating, the method for preparing the weather-resistant industrial coating comprising the following preparation steps:
[0031] (1) 6-chloro-1-hexene and 2,3-bis(2,4,5-trimethyl-3-thienyl)maleimide were added in a molar ratio of 1:1 to toluene (9 times the mass of 6-chloro-1-hexene), and triethylamine (0.04 times the mass of 6-chloro-1-hexene) was added, and the mixture was stirred at 55°C and 400 r / min for 3.5 h. The mixture was dried at 55°C under vacuum for 9 h to obtain a hexenyl ultraviolet absorber. The hexenyl ultraviolet absorber, methacrylic acid, benzoyl peroxide and n-butanol were mixed uniformly in a mass ratio of 1:1.5:0.04:7 to obtain a mixed monomer reaction solution. Bisphenol A epoxy resin was added to the mixture. Resin E51, ethylene glycol monobutyl ether and n-butanol were mixed uniformly in a mass ratio of 1:1.5:2.5, stirred at 105°C and 400r / min for 15min, and a mixed monomer reaction liquid of 1.1 times the mass of bisphenol A epoxy resin E51 was uniformly added dropwise within 30min, the temperature was raised to 121°C, and the stirring reaction was continued for 2.5h, the temperature was lowered to 82.5°C, and N,N-dimethylaminoethanol of 0.15 times the mass of bisphenol A epoxy resin E51 and deionized water of 2.5 times the mass of bisphenol A epoxy resin E51 were added, and the mixture was stirred at 650r / min for 1.5h to obtain a modified epoxy resin emulsion;
[0032] (2) 3-Chloropropyltriethoxysilane and anhydrous ethanol were mixed at a mass ratio of 1:45, the pH was adjusted to 5 with a 1 mol / L oxalic acid aqueous solution, and the mixture was stirred at 20°C and 400 r / min for 55 min to prepare a silane hydrolyzate; glass flakes and anhydrous ethanol were mixed at a mass ratio of 1:25, 9 times the mass of the glass flakes was added with the silane hydrolyzate, and the mixture was stirred at 55°C and 400 r / min for 2.5 h, filtered, washed with anhydrous ethanol for 4 times, and dried at 75°C under vacuum for 9 h to prepare pre-modified glass flakes; the pre-modified glass flakes and 3,9-dichloro-2,4- 8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide and acetonitrile were mixed uniformly in a mass ratio of 1:2.5:28, stirred at 82.5°C and 400 r / min for 12.5 min, and in a nitrogen atmosphere, 0.75 times the molar amount of 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide methylphenylsilanediol was uniformly added dropwise within 10 min, and the reaction was continued with stirring for 11 h, filtered, washed with acetonitrile 4 times, and dried at 55°C under vacuum conditions for 9 h to obtain modified glass flakes;
[0033] (3) Add 2-furanmethylamine and N-(2-aminopropyl)maleimide in a molar ratio of 1:1 to N,N-dimethylformamide (9 times the mass of 2-furanmethylamine), stir and react at 65°C and 400 r / min for 2.5 h under nitrogen protection, and dry at 55°C for 9 h under vacuum conditions to obtain a self-healing curing agent; weigh 100 parts of modified epoxy resin emulsion, 4 parts of modified glass flakes, 19 parts of self-healing curing agent, and 0.6 parts of defoaming agent, and mix them evenly. Stir at 400 r / min for 7.5 min, adjust the viscosity to 70 KU with deionized water to obtain a weather-resistant industrial coating.
[0034] Embodiment 3: A method for preparing a weather-resistant industrial coating, the method for preparing the weather-resistant industrial coating comprising the following preparation steps:
[0035] (1) 6-chloro-1-hexene and 2,3-bis(2,4,5-trimethyl-3-thienyl)maleimide were added in a molar ratio of 1:1 to toluene (10 times the mass of 6-chloro-1-hexene), and triethylamine (0.05 times the mass of 6-chloro-1-hexene) was added, and the mixture was stirred at 60°C and 500 r / min for 3 h. The mixture was dried at 60°C under vacuum for 8 h to obtain a hexenyl ultraviolet absorber. The hexenyl ultraviolet absorber, methacrylic acid, benzoyl peroxide and n-butanol were mixed uniformly in a mass ratio of 1:2:0.05:8 to obtain a mixed monomer reaction solution. Phenol A type epoxy resin E51, ethylene glycol monobutyl ether, and n-butanol were mixed uniformly in a mass ratio of 1:2:3, stirred at 110°C and 500r / min for 10min, and a mixed monomer reaction liquid of 1.2 times the mass of bisphenol A type epoxy resin E51 was uniformly added dropwise within 30min, the temperature was raised to 122°C, and the stirring reaction was continued for 2h, the temperature was lowered to 85°C, and N,N-dimethylaminoethanol of 0.2 times the mass of bisphenol A type epoxy resin E51 and deionized water of 3 times the mass of bisphenol A type epoxy resin E51 were added, and the mixture was stirred at 700r / min for 1h to obtain a modified epoxy resin emulsion;
[0036] (2) 3-Chloropropyltriethoxysilane and anhydrous ethanol were mixed at a mass ratio of 1:50, the pH was adjusted to 6 with a 1 mol / L oxalic acid aqueous solution, and the mixture was stirred at 30°C and 500 r / min for 50 min to prepare a silane hydrolyzate; glass flakes and anhydrous ethanol were mixed at a mass ratio of 1:30, 10 times the mass of the glass flakes was added with the silane hydrolyzate, and the mixture was stirred at 60°C and 500 r / min for 2 h, filtered, washed with anhydrous ethanol for 5 times, and dried at 80°C under vacuum for 8 h to prepare pre-modified glass flakes; the pre-modified glass flakes and 3,9-dichloro-2 , 4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide and acetonitrile were mixed uniformly in a mass ratio of 1:3:30, stirred at 85°C and 500r / min for 10min, and in a nitrogen atmosphere, 0.8 times the molar amount of 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide methylphenylsilanediol was uniformly added dropwise within 10min, and the reaction was continued with stirring for 10h, filtered, washed with acetonitrile 5 times, and dried at 60°C under vacuum conditions for 8h to obtain modified glass flakes;
[0037] (3) Add 2-furanmethylamine and N-(2-aminopropyl)maleimide in a molar ratio of 1:1 to N,N-dimethylformamide (10 times the mass of 2-furanmethylamine), stir and react at 70°C and 500 r / min for 2 h under nitrogen protection, and dry at 60°C for 8 h under vacuum conditions to obtain a self-healing curing agent; weigh 105 parts of modified epoxy resin emulsion, 5 parts of modified glass flakes, 20 parts of self-healing curing agent, and 0.7 parts of defoaming agent, mix well, stir at 500 r / min for 5 min, adjust the viscosity to 80 KU with deionized water, and obtain a weather-resistant industrial coating.
[0038] Comparative Example 1:
[0039] The preparation method of the weather-resistant industrial coating of Comparative Example 1 is different from that of Example 2 in that step (1) is different. Step (1) is modified as follows: methacrylic acid, benzoyl peroxide and n-butanol are mixed uniformly in a mass ratio of 1.5:0.04:7 to obtain a mixed monomer reaction liquid; bisphenol A epoxy resin E51, ethylene glycol monobutyl ether and n-butanol are mixed uniformly in a mass ratio of 1:1.5:2.5, and stirred at 105°C and 400 r / min for 1 5min, uniformly add the mixed monomer reaction solution of 1.1 times the mass of bisphenol A epoxy resin E51 dropwise within 30min, raise the temperature to 121°C, continue stirring and reacting for 2.5h, cool to 82.5°C, add N,N-dimethylaminoethanol of 0.15 times the mass of bisphenol A epoxy resin E51 and deionized water of 2.5 times the mass of bisphenol A epoxy resin E51, stir at 650r / min for 1.5h to obtain a modified epoxy resin emulsion. The remaining steps are the same as those in Example 2.
[0040] Comparative Example 2:
[0041] The preparation method of the weather-resistant industrial coating of Comparative Example 2 is different from that of Example 2 in that step (2) is not performed, and step (3) is modified as follows: 2-furanmethylamine and N-(2-aminopropyl)maleimide are added in a molar ratio of 1:1 to N,N-dimethylformamide (9 times the mass of 2-furanmethylamine), and the mixture is stirred at 65°C and 400 r / min for 2.5 h under nitrogen protection, and dried at 55°C for 9 h under vacuum conditions to obtain a self-repairing curing agent; 100 parts of modified epoxy resin emulsion, 4 parts of glass flakes, 19 parts of self-repairing curing agent, and 0.6 parts of defoaming agent are weighed and mixed uniformly, stirred at 400 r / min for 7.5 min, and the viscosity is adjusted to 70 KU with deionized water to obtain a weather-resistant industrial coating. The remaining steps are the same as those of Example 2.
[0042] Comparative Example 3:
[0043] The preparation method of the weather-resistant industrial coating of Comparative Example 3 differs from that of Example 2 only in step (3), where step (3) is modified as follows: 100 parts by mass of modified epoxy resin emulsion, 4 parts by mass of modified glass flakes, 19 parts by mass of 1,6-hexanediamine, and 0.6 parts by mass of defoamer are weighed and mixed evenly, stirred at 400 r / min for 7.5 min, and the viscosity is adjusted to 70 KU with deionized water to prepare a weather-resistant industrial coating. The remaining steps are the same as those of Example 2.
[0044] Test Example 1:
[0045] Flame retardant performance test;
[0046] Test method: Pour the examples and comparative examples into a polytetrafluoroethylene mold, cure at room temperature for 24 hours, cut the cured samples into standard specimens according to GB / T2406.2, and test the limiting oxygen index of the standard specimens. The results are shown in Table 1.
[0047] Table 1:
[0048] ;
[0049] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 1, it can be found that the weather-resistant industrial coating prepared by the present invention has good flame retardant properties.
[0050] By comparison, the limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Example 2, indicating that 3-chloropropyltriethoxysilane and glass flakes are reacted to obtain pre-modified glass flakes, chlorine atoms are introduced into the pre-modified glass flakes, and 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide and methylphenylsilanediol are dehydrochlorinated and polymerized on the pre-modified glass flakes to obtain modified glass flakes; phosphorus elements and Si-O bonds are introduced into the modified glass flakes, which decompose to produce polyphosphate and silicon dioxide during combustion, which can promote the formation of a honeycomb-like, tight carbon layer structure during combustion, reduce the generation of combustible gases, synergistically flame retardant, and give the weather-resistant industrial coating excellent flame retardant properties.
[0051] Test Example 2:
[0052] Anti-aging performance test;
[0053] Test method: Pour the embodiment and the comparative example into a polytetrafluoroethylene mold, cure at room temperature for 24 hours, cut the cured sample into standard specimens according to GB / T1040.1, test its original tensile strength with a tensile machine, irradiate the standard specimen with a xenon arc lamp for 72 hours, test the tensile strength of the standard specimen after ultraviolet aging treatment with a tensile machine, and calculate the change rate of the tensile strength of the standard specimen before and after ultraviolet aging treatment. The results are shown in Table 2.
[0054] Table 2:
[0055] ;
[0056] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 2, it can be found that the weather-resistant industrial coating prepared by the present invention has good anti-aging performance.
[0057] By comparison, the change rate of tensile strength of Examples 1 to 3 is less than that of Comparative Example 1, indicating that a hexenyl ultraviolet absorber is prepared by reacting 6-chloro-1-hexene and 2,3-bis(2,4,5-trimethyl-3-thienyl)maleimide, and a carbon-carbon double bond is introduced into the hexenyl ultraviolet absorber; the hexenyl ultraviolet absorber and methacrylic acid are grafted onto the bisphenol A epoxy resin E51 through a free radical reaction, and the hexenyl ultraviolet absorber contains a heterocyclic group-substituted diarylethylene structure, and the heterocyclic group-substituted diarylethylene has a conjugated six-electron hexatriene parent structure, and under ultraviolet light excitation, it undergoes a cis-rotational ring closure to generate a closed-ring body, and under visible light irradiation, it can undergo the opposite change to generate an open-ring body, thereby dissipating ultraviolet light energy and giving the weather-resistant industrial coating excellent anti-aging properties.
[0058] Test Example 3:
[0059] Testing of self-healing performance;
[0060] Test method: Pour the embodiment and comparative example into a polytetrafluoroethylene mold, cure at room temperature for 24 hours, cut the cured sample into standard specimens according to GB / T1040.1, and test its original tensile strength with a tensile machine. Cut a 2mm deep and 10mm long crack in the middle of the standard specimen, put it in the mold, keep it at 70℃ for 4 hours, and let it stand at room temperature for 10 hours to obtain the repaired specimen. Test its tensile strength with a tensile machine. Calculate the self-repair rate of the embodiment and comparative example, self-repair rate = (tensile strength of the repaired standard specimen / original tensile strength of the standard specimen) × 100%. The results are shown in Table 3.
[0061] Table 3:
[0062] ;
[0063] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 3, it can be found that the weather-resistant industrial coating prepared by the present invention has good self-repairing performance.
[0064] By comparison, the self-repairing rates of Examples 1 to 3 are greater than that of Comparative Example 3, indicating that the self-repairing curing agent is prepared by reacting 2-furanmethylamine and N-(2-aminopropyl)maleimide, and the furan group on 2-furanmethylamine and the maleimide group on N-(2-aminopropyl)maleimide undergo a Diels-Alder addition reaction to form a thermally reversible structure, thereby imparting self-repairing properties to the weather-resistant industrial coating; at the same time, two amino groups are introduced into the self-repairing curing agent, and the amino groups introduced into the self-repairing curing agent can react with the phosphorus-chlorine bonds on the modified glass flakes and the epoxy groups on the bisphenol A epoxy resin E51 to form a coating by curing.
[0065] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A weather-resistant industrial coating, characterized in that: The weather-resistant industrial coating is prepared by reacting a hexene-based ultraviolet absorber, methacrylic acid and bisphenol A epoxy resin E51 to obtain a modified epoxy resin emulsion; polymerizing and growing 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide and methylphenylsilanediol on pre-modified glass flakes to obtain modified glass flakes; and uniformly mixing the modified epoxy resin emulsion, the modified glass flakes, a self-repairing curing agent and a defoaming agent to obtain the weather-resistant industrial coating. The self-repairing curing agent is prepared by reacting 2-furanmethylamine and N-(2-aminopropyl)maleimide; The hexenyl ultraviolet absorber is prepared by reacting 6-chloro-1-hexene and 2,3-bis(2,4,5-trimethyl-3-thienyl)maleimide; The pre-modified glass flakes are prepared by reacting 3-chloropropyltriethoxysilane and glass flakes.
2. A method for preparing a weather-resistant industrial coating, characterized in that: The preparation method of the weather-resistant industrial coating comprises the following preparation steps: (1) Hexenyl ultraviolet absorber, methacrylic acid, benzoyl peroxide, and n-butanol are mixed uniformly in a mass ratio of 1:(1-2):(0.03-0.05):(6-8) to prepare a mixed monomer reaction liquid; bisphenol A epoxy resin E51, ethylene glycol monobutyl ether, and n-butanol are mixed uniformly in a mass ratio of 1:(1-2):(2-3), and stirred at 100-110° C. and 300-500 r / min for 10-20 min. Add a mixed monomer reaction liquid of 1 to 1.2 times the mass of bisphenol A epoxy resin E51 dropwise at a uniform speed within 30 minutes, raise the temperature to 120 to 122° C., continue stirring and reacting for 2 to 3 hours, cool to 80 to 85° C., add a salt-forming agent of 0.1 to 0.2 times the mass of bisphenol A epoxy resin E51 and deionized water of 2 to 3 times the mass of bisphenol A epoxy resin E51, stir at 600 to 700 r / min for 1 to 2 hours to obtain a modified epoxy resin emulsion; (2) Pre-modified glass flakes, 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide, and acetonitrile are mixed uniformly in a mass ratio of 1:(2-3):(26-30), stirred at 80-85°C and 300-500 r / min for 10-15 min, and in a nitrogen atmosphere, 0.7-0.8 times the molar amount of 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide is added dropwise over 10 min, stirring the reaction for 10-12 h, filtering, washing with acetonitrile for 3-5 times, and drying at 50-60°C under vacuum conditions for 8-10 h to obtain modified glass flakes; (3) According to the mass percentage, 95-105 parts of modified epoxy resin emulsion, 3-5 parts of modified glass flakes, 18-20 parts of self-healing curing agent, and 0.5-0.7 parts of defoaming agent are weighed and mixed evenly, stirred at 300-500 r / min for 5-10 min, and the viscosity is adjusted to 60-80 KU with deionized water to prepare a weather-resistant industrial coating.
3. The method for preparing a weather-resistant industrial coating according to claim 2, characterized in that: The preparation method of the hexenyl ultraviolet absorber in step (1) is as follows: 6-chloro-1-hexene and 2,3-bis(2,4,5-trimethyl-3-thienyl)maleimide are added in a molar ratio of 1:1 to toluene with a mass of 8 to 10 times that of 6-chloro-1-hexene, and triethylamine with a mass of 0.03 to 0.05 times that of 6-chloro-1-hexene is added, and the mixture is stirred at 50 to 60° C. and 300 to 500 r / min for reaction for 3 to 4 hours, and dried at 50 to 60° C. under vacuum conditions for 8 to 10 hours to obtain the hexenyl ultraviolet absorber; The reaction process is as follows:
4. The method for preparing a weather-resistant industrial coating according to claim 2, characterized in that: The salt-forming agent in step (1) is N,N-dimethylaminoethanol.
5. The method for preparing a weather-resistant industrial coating according to claim 2, characterized in that: The preparation method of the pre-modified glass flakes described in step (2) is: mix the glass flakes and anhydrous ethanol in a mass ratio of 1: (20-30), add silane hydrolyzate which is 8-10 times the mass of the glass flakes, stir and react at 50-60°C and 300-500r / min for 2-3h, filter, wash with anhydrous ethanol 3-5 times, and dry at 70-80°C under vacuum conditions for 8-10h to obtain pre-modified glass flakes.
6. The method for preparing a weather-resistant industrial coating according to claim 5, characterized in that: The preparation method of the silane hydrolyzate is as follows: 3-chloropropyltriethoxysilane and anhydrous ethanol are uniformly mixed in a mass ratio of 1:(40-50), the pH value is adjusted to 4-6 with a 1 mol / L oxalic acid aqueous solution, and the mixture is stirred at 10-30° C. and 300-500 r / min for 50-60 min to prepare the silane hydrolyzate.
7. The method for preparing a weather-resistant industrial coating according to claim 5, characterized in that: The glass flakes have a thickness of 2 to 3 μm and a flake diameter of 10 to 20 μm.
8. The method for preparing a weather-resistant industrial coating according to claim 2, characterized in that: The preparation method of the self-healing curing agent in step (3) is as follows: 2-furanmethylamine and N-(2-aminopropyl)maleimide are added in a molar ratio of 1:1 to N,N-dimethylformamide which is 8 to 10 times the mass of 2-furanmethylamine; under nitrogen protection, the mixture is stirred at 60 to 70°C and 300 to 500 r / min for 2 to 3 hours; and under vacuum conditions, the mixture is dried at 50 to 60°C for 8 to 10 hours to obtain a self-healing curing agent.
9. The method for preparing a weather-resistant industrial coating according to claim 2, characterized in that: The model of the defoaming agent in step (3) is THIX-318.
